Analysis of Common Causes of Out-of-Specification Results in the Test for Depressor Substances - TONG Xiyang; QUE Changtian; ZHANG Feng; ZHAO Lu; WANG Hongping (Shiyan dongwu yu bijiao yixue)
According to General Chapter 1145 of Division IV in the Chinese Pharmacopoeia (2020 Edition), the test for depressor substances is a common method for drug testing. It determines whether the level of depressor substances in a test sample complies with the specified standards by comparing the extent of blood pressure reduction in anesthetized cats induced by the histamine reference substance and the test sample. If an out-of-specification (OOS) result occurs in the test for depressor substances, it may be caused by inherent quality issues of the drug or errors in the testing process. Therefore, analyzing the causes of OOS is particularly important for confirming the test results and evaluating drug quality. Cats are used as experimental animals in the test for depressor substances. Compared with conventional laboratory animals, they are less stable, surgery procedures are more challenging, and the testing process is more complex. These factors make it more difficult to investigate the causes of OOS in this test. Based on a review of the literature and practical work experience, this article analyzes the causes of OOS in the test for depressor substances from the following five aspects: (1) an analysis of the impact of drug standards on OOS from three aspects: standard determination, standard content, and standard drafting; (2) personnel qualifications, including pre-employment training, compliance with standard operating procedures during experimental operations, and the ability to operate instruments; (3) factors related to cats, used as experimental animals in the test for depressor substances, including physiological characteristics, genetic background, and abnormal conditions during the experiment; (4) reference substances, reagents, test samples, and key instruments such as the multi-channel physiological signal instrument; (5) experimental operations including animal anesthesia, arterial and venous catheterization, drug administration, and data processing. This article aims to provide reference approaches for professionals engaged in the testing of pharmaceuticals and biological products when analyzing the causes of OOS in the test for depressor substances.